IMPROVING STUDENTS' WRITING ABILITY IN DESCRIPTIVE TEXT THROUGH ANIMATED FILM IN CLASS VIII SMP NEGERI 6 PADANGSIDIMPUAN - Khairunnisah, Shoufi Nisma Dewi, Rahmalia Sihite, Happy Sri Rezeki Purba (Linguistik : Jurnal Bahasa dan Sastra, 2023)
The aim of this research is to determine students' ability to write descriptive texts using animated films in class VIII SMP Negeri 6 Padangsidimpuan, and to determine the improvement in students' writing abilities in descriptive texts using animated films in class VIII SMP Negeri 6 Padangsidimpuan. The problem in this research is that students have difficulty generating their ideas, understanding grammar, and lacking vocabulary. This research uses a quantitative and qualitative approach. To collect data, researchers used quantitative and qualitative techniques. Quantitative data was collected through tests consisting of a pre-test and post-test. And qualitative data was collected through interviews and documentation. The design of this research was experimental, the research was held at SMP Negeri 6 Padangsidimpuan. The sample for this research was students in class VIII-2 of SMP Negeri 6 Padangsidimpuan, consisting of 25 students. The average Pre-test score is 59.12 and the average Post-test score is 91.52.Â  Based on the explanation above, students' ability to write descriptive text in class VIII of SMP Negeri 6 Padangsidimpuan is categorized as good and through animated films it can make students active and confident in writing.